Stress And Its Manifestation In Adolescents - Odilbekov Mansurbek Maxmudjon o‘g‘li (Next Scientists International Journal JSSHRF, 2026)
This article analyzes the concept of stress, its psychological and physiological foundations, the manifestation of stressful states during adolescence, their causes and consequences, as well as the forms of psychological support that may be applied in such situations. The influence of stress on the mental development of adolescents is explained on the basis of practical examples and scientific research.